Implementasi Projek Penguatan Profil Pelajar Pancasila melalui Pembuatan Selai dari Buah Pepaya di SDN 40 Mataram - Ramadhan Abdul Jalil; Ilda Nurdiana; Lila Aprilia; Linda Nuriyanti; Nur Mahmudi Insani (Indonesian Publication Center, 2026)
Teaching assistance is one of the independent Merdeka Belajar Kampus Merdeka (MBKM) programs facilitated by the Faculty of Teacher Training and Education (FKIP) of the University of Mataram. This program aims to provide practical experience to students in the world of education, help improve learning in schools, and make a real contribution to improving the quality of education in educational units, one of which is in the implementation of the project to strengthen the profile of Pancasila students. The method of implementing P5 mentoring for making papaya jam at SDN 40 Mataram was carried out through three stages: planning, jam making, and market day activities. The results measured were the understanding and experience of Teaching Assistant students towards the implementation of P5. Based on the results and discussions, students better understand the implementation of P5, making papaya jam. There are five dimensions developed in the mentoring of P5 activities with the theme of Entrepreneurship, namely the dimensions of Faith, Devotion to God Almighty and Noble Morals, Independence, Mutual Cooperation, Critical Reasoning, and Creativity.